Está en la página 1de 4

L x x = 0 x = L u(x, t) x t > 0

∂ 2 u = c 2 ∂ 2 u ∂t 2 ∂x 2 ,
∂ 2 u
= c 2 ∂ 2 u
∂t 2
∂x 2 ,

c 2 = T/ρ ρ T

u(0, t) = 0,

u(L, t) = 0,

t 0

 

u(x, 0) = f (x),

u t (x, 0) = g(x),

0 x L

u(x, t) = F (x)G(t),

2 u

∂t 2

= FG

∂x 2 u 2 = F G.

FG = c 2 F G,

G

c 2 G =

F

.

F

c 2 G = F

F

G

= k

.

F kF = 0

G c 2 kG = 0.

F G

u(0, t) = F (0)G(t) = 0,

u(L, t) = F (L)G(t) = 0

G 0 u = F G 0

G

0

t

F (0) = 0,

F (L) = 0.

k = 0 F

= ax + b a = b = 0 F

0 u = F G 0

k > 0 k = µ 2

F (x) = Ae µx + Be µx ,

F

k < 0 k = p 2

0

F + p 2 F = 0,

F (x) = A cos px + B sen px.

 

F (0) = A = 0

B = 0 F

0

pL = nπ,

F (L) = B sen pL = 0.

p = nπ ,

L

n Z.

B = 1 F (x) = F n (x)

F n (x) = sen nπx ,

L

n N.

k = p 2 = (nπ/L) 2

2

G + λ n G = 0

λ n = cp = cnπ L

,

G n (t) = B n cos λ n t + B n sen λ n t.

u n (x, t) = (B n cos λ n t + B n sen λ n t) sen nπx ,

L

n N.

λ n

{λ 1 , λ 2 ,

}

 

u(x, t) =

u n (x, t) =

(B n cos λ n t + B n sen λ n t) sen nπx L

.

n=1

n=1

 

u(x, 0) =

B n sen nπx

L

= f(x),

n=1

f (x)

B n =

L L

2

0

f (x) sen nπx dx,

L

n N.

∂u

∂t

t=0 =

n=1

(B n λ n

sen λ n t

+ B n λ n cos λ n t) sen nπx

L

=

n=1

B n λ n sen nπx

L

= g(x).

t=0

g(x)

λ n = cnπ/L

B n λ n =

L L

2

0

g(x) sen nπx dx,

L

2 ∗ B g(x) sen nπx dx, n ∈ N. n = cnπ L L
2
B
g(x) sen nπx dx,
n ∈ N.
n =
cnπ L
L
0